2020
DOI: 10.1038/s41598-020-60184-2
|View full text |Cite
|
Sign up to set email alerts
|

T-13 and T-26, the novel taxanes with improved oral bioavailability in rats

Abstract: www.nature.com/scientificreports www.nature.com/scientificreports/ half-life of the terminal phase (t 1/2 ) and the mean residence time (MRT). Other parameters such as maximum plasma concentration (C max ) and the time to reach C max (T max ) were also analyzed after oral administration in rats. Statistical analysis.The data were presented as mean ± standard deviation of at least three experiments.The Mann-Whitney U-test was used to investigate statistical differences at a significance level of P < 0.05. All d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Regarding diagnostic accuracy, datasets two and three indicated effectiveness of the rSDBOLD in the dataset one's regions of interest in differentiating Alzheimer Disease patients and controls. It is shown that the rSDBOLD is quite precise [2]. fMRI was able to clearly differentiate Alzheimer's disease patients from the controls, showing its potential as a biomarker for the disease.…”
Section: Functional Magnetic Resonance Imaging (Fmri)mentioning
confidence: 96%
“…Regarding diagnostic accuracy, datasets two and three indicated effectiveness of the rSDBOLD in the dataset one's regions of interest in differentiating Alzheimer Disease patients and controls. It is shown that the rSDBOLD is quite precise [2]. fMRI was able to clearly differentiate Alzheimer's disease patients from the controls, showing its potential as a biomarker for the disease.…”
Section: Functional Magnetic Resonance Imaging (Fmri)mentioning
confidence: 96%
“…These include DHP107, a mixture of paclitaxel with monoolein/tricarprylin/Tween ® 80 (DAE HWA Pharmaceutical Co., Ltd., Seoul, Republic of Korea), ModraDoc001, an amalgamation of docetaxel with polyvinylpyrrolidone-K30 and sodium lauryl sulphate [ 127 ], Orataxel (IDN-5109, BAY 59-8862) [ 128 ], Milataxel (MAC-321) [ 129 ], BMS-275183 [ 130 ], and tesetaxel (DJ-927, Genta, LaJolla, CA, USA) [ 131 ], among others. Compounds T13 and T26 have improved oral bioavailability in rats [ 132 ]. Unfortunately, the oral bioavailability of these agents in human clinical trials appears to vary significantly.…”
Section: Future Directionsmentioning
confidence: 99%